Severe Sleep Deprivation Causes Hallucinations and a Gradual Progression Toward Psychosis With Increasing Time Awake - Waters, Flavie; Chiu, Vivian; Atkinson, Amanda; Blom, Jan Dirk (Frontiers in Psychiatry, 2018)
Abstract Background: Going without sleep for long periods of time can produce a range of experiences, including perceptual distortions and hallucinations. Many questions, however, remain unanswered regarding the types of symptoms which are most reliably elicited, the time of symptom onset, and whether symptoms worsen over time towards psychotic decompensation. Since sleep deprivation exceeding 48 h is considered unethical today, an examination of historical studies with extreme sleep-loss duration is needed to obtain information about what happens during prolonged sleep loss. Methods: A systematic-review approach was used to identify experimental and observational studies of sleep deprivation in healthy people which describe the effects of prolonged sleep loss on psychopathological symptoms, without any date restriction. Results: A total of 476 articles were identified. Of these, 21 were eligible for inclusion. Duration of sleep loss ranged between 24 h and 11 nights (total 760 participants; average 72-92 h without sleep). All studies except one reported perceptual changes, including visual distortions (i.e., metamorphopsias), illusions, somatosensory changes and, in some cases, frank hallucinations. The visual modality was the most consistently affected (in 90% of the studies), followed by the somatosensory (52%) and auditory (33%) modalities. Symptoms rapidly developed after one night without sleep, progressing in an almost fixed time-dependent way. Perceptual distortions, anxiety, irritability, depersonalisation, and temporal disorientation started within 24-48 h of sleep loss, followed by complex hallucinations and disordered thinking after 48-90 h, and delusions after 72 h, after which time the clinical picture resembled that of acute psychosis or toxic delirium. By the third day without sleep, hallucinations in all three sensory modalities were reported. A period of normal sleep served to resolve psychotic symptoms in many - although not all - cases. Conclusions: Psychotic symptoms develop with increasing time awake, from simple visual/somatosensory misperceptions to hallucinations and delusions, ending in a condition resembling acute psychosis. These experiences are likely to resolve after a period of sleep, although more information is required to identify factors which can contribute to the prevention of persistent symptoms.